Identity of speech practice in the context of computer-mediated communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the problem of identity of speech practice in the context of computer-mediated communication. Syncretism of technical and humanitarian knowledge of new linguoinformational quality, advanced capabilities of review of modern speech process in the context of social and mental, psychological characteristics of the human communicational activity creates the preconditions for meta descriptions of the functioning of language various options.
Keywords: computer-mediated communication; computer-mediated discourse; linguoinformationality; metaformat; identity; culturalist; phenomenon